An Analytical Model for Dispersive Channel in Radio-over-Fiber Communication Systems Using Electro-Absorption Modulator with Chirp - Park, Minho; Sohn, Ju-Hang (International Journal of Engineering and Technology, 2019)
Chirp effects induced by the electro-absorption modulator (EAM) and chromatic dispersion from the optical fiber in the radio-over-fiber (RoF) system are critical parameters of performance for the communication system design. In this paper, the fundamental and the inter-modulation component powers are expressed by closed-form equations with respect to the dispersion and chirp. And the optical double side-band (ODSB) signals are also investigated. Therefore the power fluctuation of the fundamental and the third harmonic components are presented with expressions for two special cases, ODSB and the optical single side-band signals.Â Â